DOZ047.71: Long-gap vs. non-long-gap esophageal atresia: a prospective two-year follow-up study. (24th June 2019) - Valfre, L; Conforti, A; Scuglia, M; Aite, L; Bevilacqua, F; Iacobelli, B D; Braguglia, A; Bagolan, P
Abstract: Aim of the Study: Long-gap esophageal atresia (LGEA) represents the most challenging spectrum of esophageal atresia (EA). This condition is poorly defined, particularly regarding long-term sequelae. The aim of this study was to evaluate mid-term outcomes of patients with LGEA. Methods: A longitudinal prospective study was performed of all EA patients treated at our institution from January 2008 to December 2016. Patients were followed up in a dedicated multidisciplinary outpatient clinic. LGEA was defined as a gap wider than 3 vertebral bodies at preoperative gap measurement. Data were collected with specific attention to auxological outcomes, esophageal dilations, antireflux procedures, redo-esophageal surgery, readmission, and dysphagic problems. Chi-squared test and Mann–Whitney test were used as appropriate; P < 0.05 was considered significant. Results: During the study period, 183 EA patients were treated, 52 with LGEA. Of those, 151 reached a minimum of 1-year follow-up and were enrolled into this study. Long-gap vs non-long-gap: weight 1st year, gr; 6800 vs 8800 P < 0.0001; weight 2nd year 9500 gr vs 11000 p < 0.0001. BMI 1st year, median 14, 75 vs 15, 64 p 0.04; BMI 2nd year, median 15, 18 vs 15 p 0.9; N ° dilations 1st year, median 3 vs 1 P < 0.0001, N ° dilations 2nd year, median 1 vs 0 P < 0.0001; Nissen 1st year, n (%) 9 vs 3 p 0.0019; Nissen 2nd year, n (%) 12 vs 4 p 0.0002. Redo-esophageal surgery 1st year, n (%) 7 vs 7 p 0.14. Redo-esophageal surgery 2nd year, n (%) 8 vs 0 < 0.0001. Readmission 1st year, median 4 vs 2 P < 0.0001; readmission 2nd year, median 3 vs 0 P < 0.0001. Oral aversion 1st year, n (%) 27 vs 10 P < 0.0001; oral aversion 2nd year, n (%) 17 vs 6 P < 0.0001. Dysphagia 1st year, n (%) 25 vs 18 P < 0.0001; dysphagia 2nd year, n (%) 14 vs 19 p 0.13. Conclusions: LGEA patients underwent a more challenging course at follow-up, experiencing late auxological, more esophageal and GERD-related problems, and increased feeding and swallowing disorders in comparison with non-LGEA patients. A longer follow-up study is warranted to describe late and/or persistent problems.